ENGLISH WORD FORMATION PROCESS OF ADVERTISEMENT BOARDS IN PADANG CITY - Fenny Fauziyah; Saunir Saun (English Language and Literature, 2018)
This research purposed to analyse the type of word formation process used in advertisement boards. Sources of data obtained from advertisement boards in Padang City. Based on analysis of the data the researcher found advertisement categories that have word formation process that are smartphone, name of shop/company, funiture, course/education institutional, cigarette, event, and job vacancy. From all these categories the researcher classify word formation process into twelve types. The researcher found blending (7%), compounding (15%), borrowing (9%), coinage (9%), initialization (11%), acronym (4%), clipping (15%), back formation (5%), inflection (11%), derivation (7%), onomatopoeia (2%), cliticization (5%). The result of this research indicate advertisement category that many found in advertisment boards in Padang city is name of shop/company. And the advertisement category that rarely found in advertisment boards in Padang city is job vacancy. In addition, based on analysis of the data show that compounding and inflection are types that many used in advertisment boards in Padang city. And type that rarely used in advetisement boards is onomatopoeia.